A cross-sectional analysis of the factors that shape adult nursing students' values, attitudes and perceptions of compassionate care. (March 2017) - McSherry, Wilfred; Bloomfield, Sarah; Thompson, Roy; Nixon, Valerie A; Birch, Carole; Griffiths, Nicola; Fisher, Shani; Boughey, Adam J
Nursing students are the future of nursing, and are situated between the expectation of the public (that the public will receive compassionate care) and the profession (that the profession will continue to develop technically to meet the needs of the changing healthcare economy). Research has focused on the factors affecting registered nurses' values in care. However, less is known regarding the factors that shape nursing students' values, attitudes/and perceptions of compassionate care. Six focus group discussions with 23 adult branch nursing students (years 1–3) from a UK university were conducted to ascertain the nursing students' understanding of personal and professional values, factors influencing these values, and whether they felt these values influenced the way they provided compassionate care. Qualitative thematic analysis resulted in five themes, three of which were the focus of this paper: general values, fundamental nursing and nursing values. Participants considered a range of influencers of their general values, and demonstrated a transparency between their personal and professional values, with respect and dignity being important. Fundamental nursing was complex to consider but was considered to orientate around the provision of care in a compassionate way.